Exposure to Temperature and Insecticides Modulates the Expression of Small Noncoding RNA-Associated Transcripts in the Colorado Potato Beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae). Issue 1 (16th February 2022) - Ben Youssef, Mariem; Christelle Ouédraogo, Brigitte; Bastarache, Pierre; Dumas, Pascal; Moffat, Chandra E; Vickruck, Jessica L; Morin, Pier Jr
Abstract: The Colorado potato beetle ( Leptinotarsa decemlineata (Say)) is an insect that can adapt to various challenges, including temperature fluctuations or select insecticide treatments. This pest is also an ongoing threat to the potato industry. Small noncoding RNAs such as miRNAs, which can control posttranscriptionally the expression of various genes, and piRNAs, which can notably impact mRNA turnover, are modulated in insects under different conditions. Unfortunately, information regarding the expression status of key players involved in their synthesis and function is for the most part lacking. The current study thus aims at assessing the levels of such targets in L. decemlineata exposed to hot and cold temperatures as well as treated to the insecticides chlorantraniliprole, clothianidin, imidacloprid, and spinosad. Transcript expression levels of Ago1, Ago2, Ago3, Dcr2a, Dcr2b, Expo-5, Siwi-1, and Siwi-2, components of pathways associated with small noncoding RNA production or function, were measured by qRT-PCR and revealed modulation of select transcripts in response to temperature challenges and to select insecticides. RNAi-mediated reduction of Ago2 transcript levels in L. decemlineata injected with Ago2-targeting dsRNA and exposed to cold and warm temperatures was also conducted. Changes in survival rates were observed for the latter condition in dsRNA- versus saline-injected insects. These results showcase the differential expression of select targets involved in small noncoding RNA homeostasis and provide leads for the subsequent assessment of their involvement during stress response in L. decemlineata using RNAi-based approaches.